2019
DOI: 10.1111/asj.13226
|View full text |Cite
|
Sign up to set email alerts
|

Myosin: Formation and maintenance of thick filaments

Abstract: Skeletal muscle consists of bundles of myofibers containing millions of myofibrils, each of which is formed of longitudinally aligned sarcomere structures. Sarcomeres are the minimum contractile unit, which mainly consists of four components: Z‐bands, thin filaments, thick filaments, and connectin/titin. The size and shape of the sarcomere component is strictly controlled. Surprisingly, skeletal muscle cells not only synthesize a series of myofibrillar proteins but also regulate the assembly of those proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…How interaction of MyBP-C with myosin enhances the SRX state is another fertile but challenging area of investigation, which may require cryo-electron tomography of thick filaments or intact myofibrils ( Burbaum et al, 2021 ) or single particle cryo-EM studies of MyBP-C–IHM complexes. Experiments suggest that thick filaments in muscle are in equilibrium with a pool of myosin monomer, which may play a role in thick filament assembly/disassembly during development, hypertrophy, and myosin turnover ( Saad et al, 1986 ; Katoh et al, 1998 ; Ojima, 2019 ). Myosin monomers at physiological ionic strength form IHMs with a folded tail structure and slow ATP turnover rate, which may act as a transport form from ribosome to filament ( Ankrett et al, 1991 ; Katoh et al, 1998 ; Jung et al, 2008 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…How interaction of MyBP-C with myosin enhances the SRX state is another fertile but challenging area of investigation, which may require cryo-electron tomography of thick filaments or intact myofibrils ( Burbaum et al, 2021 ) or single particle cryo-EM studies of MyBP-C–IHM complexes. Experiments suggest that thick filaments in muscle are in equilibrium with a pool of myosin monomer, which may play a role in thick filament assembly/disassembly during development, hypertrophy, and myosin turnover ( Saad et al, 1986 ; Katoh et al, 1998 ; Ojima, 2019 ). Myosin monomers at physiological ionic strength form IHMs with a folded tail structure and slow ATP turnover rate, which may act as a transport form from ribosome to filament ( Ankrett et al, 1991 ; Katoh et al, 1998 ; Jung et al, 2008 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…The tail domain is responsible for myosin coiled-coil dimerization and the bivalent nature of most myosins. These domains are also isoform-specific and can associate with various distinct cellular cargo, membrane-spanning motifs, as well as forming the shaft of the thick filament [ 64 , 65 , 66 , 67 ].…”
Section: Introduction To Myosin Structurementioning
confidence: 99%
“…In this study, transcriptome and annotation identified nine families of flight muscle structural proteins in S. frugiperda , with myosin and actin showing higher number of transcripts ( Table 2 ). Myosin is a superfamily of molecular motors that move along the track of actin filaments, which accounts for 60% of the total protein of myofibrils and plays a role in muscle contraction [ 63 ]. One flightin-encoding gene was also found in S. frugiperda .…”
Section: Discussionmentioning
confidence: 99%